56. Syntaxonomical and nomenclatural notes about rupicolous communities of Jasonio glutinosae-Teucrietum thymifolii - Alonso, Mª Ángeles; Juan, Ana; Benito Crespo, Manuel; Agulló, Jonás César; Villar, José Luis (Lazaroa, 2011)
In the present contribution, the nomenclature of the casmophyte community Jasonio-Teucrietum thymifolii is reviewed, with a new arrangement including four territorial sub-associations. First, the correct authority and publication date for the association is Jasonio-Teucrietum thymifolii Mateo 1983. Two new combinations are stated: Jasonio-Teucrietum thymifolii subass. jasonietosum glutinosae (O. Bolòs 1967) Agulló, M.A. Alonso, A. Juan, J.L.Villar & M.B. Crespo comb. nov., and Jasonio-Teucrietum thymifolii subass. galietosum moralesiani (Sánchez-Gómez & Alcaraz 1993) Agulló, M.A. Alonso, A. Juan, J.L. Villar & M.B. Crespo comb. nov. et nom. corr. Furthermore, a new sub-association is described for the Meridional- Murcian territories (Jasonio-Teucrietum thymifolii subass. centaureetosum willkommii Agulló, M.A. Alonso, A. Juan, J.L. Villar & M.B. Crespo subass. nova). Ecological, bioclimatic, biogeographical and chorological data are reported for each accepted syntaxon. In addition, a new taxonomic combination is proposed: Galium boissieranum subsp. Moralesianum (Ortega Oliv. & Devesa) Agulló, M.A. Alonso, A. Juan, J.L. Villar & M.B. Crespo.